Penerapan Model Pembelajaran Discovery Learning Berbantuan Powerpoint Pada Siswa SMPN 1 Pakusari - Qibtiyah, Mariatul; Susilaningtyas, Tri; Styo Siskawati, Fury (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
Discovery Learning is one alternative learning model in the 2013 curriculum. The facts in the field of teachers have never developed a discovery learning model. Student learning outcomes based on the average test score have not reached the Minimum Completeness Criteria (KKM). One media that can be a helper for communication students research is Powerpoint. The purpose of this study is to describe the implementation of the discovery learning model assisted by Powerpoint on the cube and block material at SMPN 1 Pakusari. The research used a qualitative descriptive research design. Based on the results of the study, it can be concluded that the researcher carried out the steps of the learning implementation plan using the powerpoint-assisted discovery learning model.